The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/aoc.6149
|View full text |Cite
|
Sign up to set email alerts
|

Co (II), Cu (II), Mn (II), Ni (II), Pd (II), and Pt (II) complexes of bidentate Schiff base ligand: Synthesis, crystal structure, and acute toxicity evaluation

Abstract: 5‐methoxy‐2‐(((2chloro‐5‐(trifluoromethyl)phenyl)imino)methyl)phenol) (HL) and its cobalt (II), copper (II), manganese (II), nickel (II), palladium (II), and platinum (II) complexes, [Co(L)2]·4H2O (1), [Cu(L)2] (2), [Mn(L)2(H2O)2]·H2O (3), [Ni(L)2] (4), [Pd(L)2] (5), [Pt(L)2] (6), were synthesized and characterized. The compounds were investigated by different physico‐chemical techniques including IR, 1H‐NMR, 13C‐NMR, UV‐Vis, mass spectroscopies, elemental and thermal analysis, magnetic susceptibility measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…In metal complexes, this band is shifted to lower wavenumber by 10–11 cm −1 indicating the participation of the azomethine nitrogen in coordination. [ 30 ] In the free ligand spectrum, a broad band located at 3438 cm −1 due to the phenolic ν (OH) group is disappeared in all complexes suggesting the phenolic‐OH group participation in coordination. Involvement of the deprotonated phenolic‐OH group in chelation is confirmed by the blueshift of the ν (C–O) band (shift from 1173 cm −1 to lower frequency ranging 1157–1159 cm −1 ) in the complexes.…”
Section: Resultsmentioning
confidence: 99%
“…In metal complexes, this band is shifted to lower wavenumber by 10–11 cm −1 indicating the participation of the azomethine nitrogen in coordination. [ 30 ] In the free ligand spectrum, a broad band located at 3438 cm −1 due to the phenolic ν (OH) group is disappeared in all complexes suggesting the phenolic‐OH group participation in coordination. Involvement of the deprotonated phenolic‐OH group in chelation is confirmed by the blueshift of the ν (C–O) band (shift from 1173 cm −1 to lower frequency ranging 1157–1159 cm −1 ) in the complexes.…”
Section: Resultsmentioning
confidence: 99%
“…nauplii gut has noticeable changes as observed by a phase-contrast microscope, as shown in Figure . The results suggested that complex 1 accumulation does not induce mortality after 24 h of exposure. …”
Section: Resultsmentioning
confidence: 95%
“…Crustaceans of the species Artemia franciscana Kellogg were used to determine the toxicity of the new pyrrole derivatives on the animal cell. The test assesses how many of the crustacean nauplii die in 24 h and 48 h intervals from the contact with the solutions of the tested compounds [53][54][55][56][57].…”
Section: Animal Toxicity Assay Artemia Franciscana Toxicity Assaymentioning
confidence: 99%